Possible Mechanisms by Which Topical 5-Fluorouracil and Dermabrasion Could Induce Pigment Spread in Vitiligo Skin: An Experimental Study. (9th April 2013) - Gauthier, Y.; Anbar, T.; Lepreux, S.; Cario-André, M.; Benzekri, L.
Abstract : The combination of skin ablation and 5-Fluorouracil (5-FU) ointment was previously tried in the treatment of vitiligo, and good results were specifically reported in glabrous skin without follicular melanocyte reservoirs. Methods . This study was carried out on the skins of seven guinea pigs: three were treated with mechanical dermabrasion plus topical 5-FU in an achromic area contiguous to a pigmented area; two were treated by only dermabrasion in a similar area; and two were treated by topical 5-FU alone. Clinical, histological, and ultrastructural studies were performed over two months. Results . In guinea pigs treated with dermabrasion plus 5-FU, we observed firstly a delay of wound healing with an obvious inflammatory reaction, and, after two months, evident pigment spread from the pigmented into the achromic area. After six months, we noticed black hair regrowing in the achromic area. Pigment spread was not seen in the guinea pigs skin treated by either dermabrasion or topical 5-FU. We suggest that the inflammatory mediators and enzymes (metalloproteinases), which are locally released over a long time, could stimulate and facilitate melanocyte proliferation and migration through the enlarged intercellular spaces of the epidermis. This sequence of events may be applied to vitiligo patients treated with 5-FU on ablated lesions.